A non‐destructive approach for doping profiles characterization by micro‐Raman spectroscopy: the case of B‐implanted Ge. (16th January 2014) - Sanson, A.; Napolitani, E.; Carnera, A.; Impellizzeri, G.; Giarola, M.; Mariotto, G.
<x xml:space="preserve">Abstract</x> B‐implanted Ge samples have been investigated by micro‐Raman spectroscopy under different excitation wavelengths, with the aim of gaining insights about the B distribution at different depths beneath the sample surface. The intensities, observed under the different excitation wavelengths, of the B–Ge Raman peak at about 545 cm−1, which is due to the local vibrational mode of the substitutional B atoms in the Ge matrix, have been used to calibrate the optical absorption lengths in B‐implanted Ge. Then, by using these calibrated values, a very sharp correlation between the spectral features of the Ge–Ge Raman peak at 300 cm−1 and the content of substitutional B atoms has been derived. Accordingly, a non‐destructive approach, based on micro‐Raman spectroscopy under different excitation wavelengths, is presented to estimate, at least at the lowest depths, the carrier concentration profiles from the spectral features of the Ge–Ge Raman peak. Copyright © 2014 John Wiley & Sons, Ltd.